Spatial distributions of media kinetic energy as measured by positron emission particle tracking in a vertically stirred media mill. (November 2016) - Riley, M.; Pinkney, S.; Blackburn, S.; Rowson, N.A.
Highlights: The vertically stirred media mill is visualised using PEPT. Relationships between media position and KE in the mill are explored. The effect of tip speed on media KE and spatial distributions is investigated. Media motion is tracked over short and long time scales. Abstract: The stirred media mill is a piece of process equipment used in comminution, which uses grinding media, beads of ceramic or similar material, to mediate energy transfer between a rotating impeller and a slurry of the particles to be ground. Motion of the media is vital to the action of the mill, but is often assumed to be simple in modelling due to incomplete knowledge in detail. The movement of a media particle in a stirred media mill has been observed using Positron Emission Particle Tracking. The occupancy and the kinetic energy of the particle within the mill have been calculated and plotted in order to examine the effect of tip speed on the particle. The particle path has been shown to be different below, at, and above the impellers indicating the media are subject to different forces in the region of the impellers. Changes in velocity of the particle correspond with changes of height of the particle in the mill, caused by the particle colliding with the impellers. The impeller speed was found to significantly affect media KE distribution in the mill. At higher tip speeds the media particle has lower energy outside the impeller zone compared to in the impeller zone indicating that there is significantly less energy transfer between the zones when the tip speed is increased. Additionally, at high tip speeds the occupancy is low in the high kinetic energy region at the impellers.